ANALISIS PEMBATALAN AKTA HIBAH SAHAM DIDASARKAN PADA PERJANJIAN INVESTOR YANG TELAH DIBATALKAN (STUDI PUTUSAN KASASI NOMOR 2820 K/PDT/2014) - Su Hyon Son; Stanislaus Atalim (Jurnal Hukum Adigama, 2018)
According to article 1313 of Civil Code, the definition of an agreement is an act pursuant to which one or more individuals commit themselves to one another. Theoretically, an agreement that was made based on a previous made agreement makes this two agreements relate to one another and put them into a condition where the previous made agreement can terminate other agreement that has an attachment to it. This study is a normative legal research, where the results of this study are : first, the Judges’ decision to terminate a grant deed was null and void by one of its considerations that was based on an investor agreement that by fact was made after the grant deed and had been canceled before the lawsuit was brought to court that made the decision uncertain. Second, the investor's agreement should not be taken as one of the judges' consideration to terminate the deed of grant, seeing that the two agreements are not related and can’t be categorized as principal agreement and accesoir agreement. They both also have different standing in which the deed of grant is an notarial deed whereas the investor agreement is a private deed. So, the investor agreement can only be used as an evidence in court and cant be used as one of the judges' considerations to terminate the deed of grant.